2006
DOI: 10.1136/sti.2005.017111
|View full text |Cite
|
Sign up to set email alerts
|

Trends in antenatal HIV prevalence in urban Uganda associated with uptake of preventive sexual behaviour

Abstract: The ecological correlation between the trends in HIV prevalence and incidence and the increase in protective sexual behaviour during the 1990s makes a compelling case for continuing prevention efforts in Uganda.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
45
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 10 publications
7
45
0
Order By: Relevance
“…1,9,10 Although there is new evidence of an increase in HIV infections in some parts of Uganda, 12 several other studies in both urban and rural areas have shown a tremendous decline in HIV prevalence associated with increased awareness and significant decrease in sexual behavior at risk. [12][13][14][15][16][17][18][19][20][21][22] The Uganda National sero and behavioural survey 2004/5 10 showed adult HIV prevalence declined from 18-30 % in the early 1990s to 6.4% in 2005. The report further showed an estimated 1.1 million Ugandans living with the HIV/AIDS in 2005 with lowest prevalence in the West Nile region (2.3%) and highest prevalence in Central region (8.5%), followed by North ern region (8.2%), Western region (6.9%) and Eastern region (5.3%).…”
Section: Introductionmentioning
confidence: 99%
“…1,9,10 Although there is new evidence of an increase in HIV infections in some parts of Uganda, 12 several other studies in both urban and rural areas have shown a tremendous decline in HIV prevalence associated with increased awareness and significant decrease in sexual behavior at risk. [12][13][14][15][16][17][18][19][20][21][22] The Uganda National sero and behavioural survey 2004/5 10 showed adult HIV prevalence declined from 18-30 % in the early 1990s to 6.4% in 2005. The report further showed an estimated 1.1 million Ugandans living with the HIV/AIDS in 2005 with lowest prevalence in the West Nile region (2.3%) and highest prevalence in Central region (8.5%), followed by North ern region (8.2%), Western region (6.9%) and Eastern region (5.3%).…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between condom use and HIV infection can suffer from problems of bidirectionality (e.g., see Kajubi et al, 2005). However, longitudinal studies and meta-analyses of population-based studies have provided strong evidence of the association between condom use and declines in HIV prevalence (Kirungi et al, 2006;Sandoy, Michelo, Siziya, & Flykesnes, 2007;Stoneburner & Low-Beer, 2004). Future research studies would be strengthened by prospective examination of the associations between the key measures of parental investment and associational membership and direct measures of HIV infection among young men and women in South Africa and elsewhere.…”
Section: Study Limitationsmentioning
confidence: 99%
“…The sentinel surveillance system from which national HIV prevalence estimates were initially derived was established in 1989 starting with six clinics in urban areas but later expanded to include clinics from peri-urban and rural areas (Garbus & Marseille, 2003). HIV prevalence was estimated at 15% among all adults (15-49 years) in 1991-1992 which was considered to be the peak of the epidemic in the country (Kirungi et al 2006;Stoneburner & Low-Beer, 2004). This, however, declined to 7% in 2001 and was still at this level in 2009 (Joint United Nations Programme on HIV/AIDS [UNAIDS], 2010; Kirungi et al 2006;Stoneburner & Low-Beer, 2004).…”
Section: Contextmentioning
confidence: 99%
“…HIV prevalence was estimated at 15% among all adults (15-49 years) in 1991-1992 which was considered to be the peak of the epidemic in the country (Kirungi et al 2006;Stoneburner & Low-Beer, 2004). This, however, declined to 7% in 2001 and was still at this level in 2009 (Joint United Nations Programme on HIV/AIDS [UNAIDS], 2010; Kirungi et al 2006;Stoneburner & Low-Beer, 2004). As in other sub-Saharan Africa countries affected by the epidemic, HIV prevalence is higher among women than among men and in the urban compared to rural areas.…”
Section: Contextmentioning
confidence: 99%